Navigating the Common Core with English Language Learners practical strategies to develop higher-order thinking skills - Ferlazzo, Larry; Hull-Sypnieski, Katie 1974- (Jossey-Bass, 2016)
"Written by experienced teachers of English Language Learners, this essential resource gives educators a much-needed and practical guide for implementing the Common Core State Standards in ELL classrooms. Larry Ferlazzo and Katie Hull Sypnieski provide a digest of the latest research and developments in ELL education, along with comprehensive guidance in reading and writing, social studies, math, science, social/emotional learning and more. The book's expert guidance helps instructors instill the higher-order thinking skills demanded by the Common Core, and its ready-to-use lesson plans and reproducible handouts help educators bring key ideas and concepts to life in the classroom."--Back cover.